Barriers to HIV Testing Within a Sample of Spanish-speaking Latinx Gay, Bisexual, and Other Men Who Have Sex with Men: Implications for HIV Prevention and Care - Danielle N. Horridge (New Prairie Press, 2019)
Gay, bisexual, and other men who have sex with men (GBMSM) have higher rates of HIV infection compared to the general population in the United States, and the infection rate is growing among Latinx GBMSM, compared to a decline in most other demographic subgroups. Uptake of pre-exposure prophylaxis (PrEP), a biomedical strategy designed to reduce HIV transmission, is very low among Latinx GBMSM. HIV testing is a critical first step in the HIV prevention and care continua. We analyzed data from a community-based sample of Latinx GBMSM in the southeastern United States to identify the most common HIV testing barriers and the factors associated with barriers. The five most commonly reported HIV testing barriers included not knowing where to get tested, not having health insurance, fear of being HIV positive, practicing safer sex and perceiving not needing to be tested, and not being recommended to get tested. Using multivariable logistic regression modeling, speaking only Spanish, being unemployed, and adhering to traditional notions of masculinity were associated with increased barriers to HIV testing. We recommend that interventions to increase HIV testing among Latinx GBMSM be provided in Spanish and use culturally congruent messaging, be accessible to those who are unemployed, and incorporate positive risk-reducing aspects of masculinity.